PENDAMPINGAN BELAJAR SISWA DI DESA LEUWIDAMAR LEBAK BANTEN - Ende Ende; Reza Maulana; Maya Nuraeni; Masuroh Masuroh; Sarah Octavian (Gapenas Publisher, 2022)
Leuwidamar Village is one of the villages located in Leuwidamar District, Lebak Regency, Banten Province, which is located north of the sub-district center. The education aspect in Leuwidamar Village is one of the villages in Lebak Regency with a relatively low level of education. The results of the learning activities carried out had an impact on increasing the ability to read and simple arithmetic of the 30 students